UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE DEMONSTRASI PADA KONSEP BERBAGAI BENTUK ENERGI DAN MANFAATNYA DALAM KEHIDUPAN SEHARI-HARIPADA MATA PELAJARAN IPA KELAS 1 SD NEGERI 58 REJANG LEBONG - Nujanah, Nurjanah (Jurnal PGSD, 2017)
Research entitled Improving Student Results through Demonstration Methods On Concepts Various Forms of Energy and Benefits in Everyday Life In Science Subject Class 1 SD Negeri 58 Rejang Lebong "The purpose of this research is to increase students' understanding of the various subjects and activities of students in the learning process. How can students not forget the lesson material they have received so that students will be ready to face upgrading tests that are ready or not ready to face. How to make a teaching material so as not to be forgotten by the students. In this case the teacher must find a method to remind all the memory in the mind of the students they have received. The teacher must be able to revive the memory.This research uses action research for two cycles. Each cycle consists of stages: design, activity and observation, reflection, and revision. Target of this research is student of Class I SD Negeri 58 Rejang Lebong, The data obtained in the form of formative test result, observation sheet of learning activity The result of research from cycle I and cycle II from data collected indicate a significant increase of achievement, so that. It can be concluded that through concrete objects media student learning outcomes can be improved.